(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Break in the continuity of skin is known as wound. Nature has given tremendous natural capacities to human being to heal wounds. The processes of healing get activated immediately after the trauma and continue till the formation of a healthy scar in a sequential manner. This normal response gets disrupted in different conditions like slough, infection, blood supply to the area, presence of foreign bodies, unhygienic treatments, and general factors like nutritional conditions, presence of systemic diseases etc. Wound healing process can be facilitated by natural products with medicinal properties. Many studies on the wound healing properties of natural products with anti-inflammatory, antioxidant, antibacterial and pro-collagen synthesis actions have been conducted. Panchavalkala was studied in different forms like gel, decoction, ointment, sanitizer, Ghanasatwa, Taila, Ghrita and cream. In all forms it has proved its efficiency for wound healing. This article is aimed to review and summarized the preclinical and clinical research studies conducted on wound healing activities of Panchavalkal in the different forms like extract, gel, ointment, douche, Kwath etc. Exciting clinical and preclinical studies found with very good healing property of Panchavalkala.